An uncontrolled trial of multi‐component care for first‐episode psychosis: Effects on social cognition. Issue 3 (25th January 2017) - Breitborde, Nicholas J. K.; Moe, Aubrey M.; Woolverton, Cindy; Harrison‐Monroe, Patricia; Bell, Emily K.
Abstract : Growing evidence suggests that specialized, multi‐component treatment programmes produce improvements in numerous outcomes among individuals with first‐episode psychosis. However, these programmes often lack interventions specifically designed to address deficits in social cognition. This raises questions about the effectiveness of such programmes in addressing deficits in social cognition that accompany psychotic disorders. We investigated the effect of participation in a multi‐component treatment programme on social cognition among 71 individuals with first‐episode psychosis. Participants experienced gains in emotion processing, social knowledge, social perception and theory of mind. However, after controlling for multiple comparisons, these improvements were limited to theory of mind and recognition of social cues in low emotion interactions. Although our findings should be interpreted cautiously, they raise the possibility that individuals participating in multi‐component treatment programmes for first‐episode psychosis without interventions specifically targeting social cognition may still experience gains in social cognition.